Measurement of Sigma Level from Consumer Sound Side in Fried Oil Product - Julianus Hutabarat; Riwayati Triswanti; Renny Septiari (IPTEK Journal of Proceedings Series, 2020)
The industry of goods and services is inseparable and is highly related to customers, so customer satisfaction is always the main goal. A company will be able to continue to survive in the market as long as it can maintain good quality in order to satisfy customers. To find out which cooking oil products on the market are in accordance with the wishes of the customer or the voice of customer, a customer satisfaction survey or questionnaire was conducted which was distributed to mothers in Griya Asri housing complex, Purwosari - Pasuruan, by comparing 3 brands of cooking oil which were all made from oil palm, namely: brands A, B and C. From the questionnaire will be known what is needed or desired by the customer so the company can determine CTQ (critical to quality) based on the voice of customer. The questionnaire that has been distributed is then calculated sigma level and also made a comparison between the level of importance with the level of customer satisfaction. The results show that the lowest level of sigma for brand A cooking oil in CTQ is not turbid fast and cheap price is 1.86, with the position in quadrant A (Attention) while for B brand low level sigma cooking oil is in CTQ for low price, namely 1.83 with a position in quadrant A (Attention) and finally the lowest level of sigma for C brand cooking oil is in CTQ Not quickly cloudy, that is 1.97 with a position in quadrant A (Attention). So it can be concluded that the CTQ that needs to be improved and considered both from the sigma level and the quadrant position for the three types of cooking oil products is not turbid fast and cheap prices.